inggris inggris - Hanum Setyaningrum; Ririn Ambarini; Siti Nur'Aini (ELP (Journal of English Language Pedagogy), 2026)
This study aims to investigate the effectiveness of integrating subtitled YouTube videos with reading worksheets to enhance vocabulary mastery and reading comprehension among 10th-grade senior high school students in the EFL context. The primary research problems addressed include students’ limited vocabulary hindering text comprehension and the suboptimal impact of standalone videos without supplementary activities. Employing a quantitative pre-experimental design with a single-group pretest and posttest, the research involved 35 students from class 10 at MA Darut Taqwa Semarang. Interventions spanned five sessions using validated reading worksheets (initially 21 valid items with Cronbach’s ? = 0.903), analyzed via the Wilcoxon signed-rank test due to non-normal data distribution. The findings show that the integration of subtitled videos and worksheets significantly improved students’ vocabulary and reading performance. This indicates that multimodal learning more effective than video alone in supporting comprehension, retention, and engagement. In conclusion, the integration offers a cost-effective, adaptable model for EFL instruction in resource-limited madrasahs, with implications for digital curriculum development.